Investigation of the relationship between rheumatoid factor positivity and parvovirus B19 seropositivity - Akbulut, H. Handan; Ozden, Mehmet; Celik, Ilhami; Koca, S. Serdar; Bulut, Vedat (Ortadogu Ad Pres & Publ Co, 2007)
Objective: It is suggested that the Human Parvovirus B19 (HPV B19) can be responsible for the etiology or triggering the autoimmune diseases that affecting joints and connective tissues in adults and children. In this study, the possible relationship between HPV B19 IgM and IgG antibodies and rheumatoid factor (RF) positivity was investigated in patients with (RF) positivity who admitted to Department of Rheumatology with complaints of common arthralgia and locomotor system. Material and Methods: RF positive 50 patients and 20 healthy volunteers were included in the study. The levels of anti-HPV B19 IgM and IgG antibodies (with ELISA), ANA with IFA on Hep-2 cells and CRP with nephelometry were studied in serum samples obtained from the patients and controls. Results: Although the rate of anti-HPV B19 IgM positivity was higher in patients than controls this was not statistically significant (p> 0.05). No significant difference was observed between Anti-HPV B19 IgG positivity of the patients and controls (p> 0.05). 46% ANA positivity was detected in RF positive patients, no ANA positivity was observed in RF negative controls (p< 0.05). No statistically significant difference was observed in terms of HPV B19 IgM and IgG antibody positivity in patients who had rheumatoid arthritis or not. HPV B19 IgM positivity was highly significant in patients with ANA positivity than those without ANA positivity. Conclusions: No significant relationship was observed with the parvovirus infections of the patients who had complaint of arthralgia and problems of locomotors system with RF positivity. However, significance of HPV B19 IgM positivity in patients with ANA positivity was interpreted that it was verified the probable relationship between the autoimmune diseases and parvovirus infections.
Romatoid faktör pozitifli?i i?le parvovirüs B19 seropozitifli?i arasindaki i?lişkinin araştirilmasi
Keywords: parvovirus B19; human; rheumatoid factor; antibodies; antinuclear